On ℛ4 Terms and MHV Amplitudes in N=5,6 Supergravity Vacua of Type II Superstrings - Massimo Bianchi (Advances in High Energy Physics)
We compute one-loop threshold corrections to ℛ4 terms in N=5,6 supergravity vacua of Type II superstrings. We then discuss nonperturbative corrections generated by asymmetric D-brane instantons. Finally we derive generating functions for MHV amplitudes at tree level in N=5,6 supergravities.